UPAYA MENJAGA KESEHATAN MANUSIA DARI-PENGARUH RADIASI ELEKTROMAGNETIK - Sukardiyono Sukardiyono; Supahar Supahar (LPMPP Universitas Negeri Yogyakarta, 1999)
It is not avoidable that today's human life cannotbe separated from the need for electric energy. SriSoewasti Soesanto (1996: 6) states that many studieshave shown the effects of the electromagnetic fieldcaused by electrical equipment on human health in theform of leukemia, brain cancer, and barrenness. Becausethere is such an indication that the radiation ofthe electromagnetic field is dangerous for human health,preventive measures have, therefore, to be taken to reducethe negative effects by avoiding direct contact withthe source of radiation, by providing a protective coverappropriate with the kind of radiation, by putting asfar a distance as possible between the body and thesource of radiation, by shortening the period of workusing the source of radiation, and so on.